Consolidação e cotidiano de uma instituição do Império: a Polícia Militar do Espírito Santo (1835/1889) - Baptista, Josette (2009)
Describes the trajectory of the Military Police in the State of Espírito Santo since its creation in 1835 until the fall of the Empire, using as sources the reports of the President of Province, laws and decrees of the Empire and Province, and more two documents produced by the police: the Book´s Records of Settlements of the police officers and the Daily Maps. Displays the constant clash between the Presidents of the Province and members of the Assembly regarding the need of the police to that society, in which the former always pointed to the need of increasing the number of police officers, while the latter tended to their decline, and even extinction as occurred in 1844. Also indicates the institutional routine of police from the format of the profile of people who become police officers in those days of the Empire. This profile had been portrayed through charts and graphs that enable us to provide detailed analysis about the affiliation, place of birth, age, color, marital status, previous office, time of remaining, form of entry, reason for licensing, promotion, discipline, and what did the police officers in the daily performance of their offices. Concludes that the police was a institution that arose in the context of the building of the own State, and thus contributed to its configuration in Brazil.